Management of Hypertension in the Elderly Patient at Abidjan Cardiology Institute (Ivory Coast) - K. E. Kramoh; E. Aké-Traboulsi; C. Konin; Y. N'goran; I. Coulibaly; A. Adoubi; J. Koffi; J. B. Anzouan-Kacou; M. Guikahue (International Journal of Hypertension)
Background. Since the treatment of hypertension is beneficial for the elderly, we have undertaken this study that aims to evaluate the management of hypertension in elderly patient in Côte d'Ivoire. Methods. A retrospective study was conducted among 854 hypertensive elderly patients of Abidjan Cardiology Institute who were followed for a minimum of one year, between January 2000 and December 2009. Results. The patients mean age was 73.1±5.3 years, and 59% were women. At the first presentation, it was mostly systolic-diastolic hypertension (51.8%) and isolated systolic hypertension (38.5%). Mean blood pressure was 169.4±28.4 mmHg for systolic, 95.3±15.7 mmHg for diastolic, and 74.1±22.8 mmHg for pulse pressure. Pulse pressure was ≥60 mmHg in 80.4%. According to the European Guidelines stratification of the cardiovascular risk-excess attributable to high blood pressure, 82.1% of the sample had a very high added risk. The pharmacological therapy was prescribed in 93.5%. More than 66% of patients were receiving ≥2 antihypertensive drugs including fixed-dose combination drugs. The most common agents used were diuretics (63.5%) followed by angiotensin-converting enzyme inhibitors or angiotensin receptor blockers in 61.3%. The most common agents used for monotherapy were calcium antagonists. When ≥2 drugs were used, diuretics and angiotensin-converting enzyme inhibitors or angiotensin receptor blockers were the most common. Blood pressure control was achieved in 42.6%. Conclusion. The control of elderly hypertension can be effective in Sub-Saharan Africa. He required at least two antihypertensive drugs to meet the recommended blood pressure target.